Gain of 1q is a marker of poor prognosis in Wilms' tumors. Issue 11 (4th September 2013) - Segers, H.; van den, M. M.; Williams, R. D.; van, H.; Vujanic, G.; Pieters, R.; Pritchard‐Jones, K.; Bown, N.
<x xml:space="preserve">Abstract</x> Wilms' tumor (WT) trials aim to better tailor treatment intensity to the risk of relapse and death. Currently, stage, histology, age (< or > 24 months), and combined loss of heterozygosity at 1p and 16q in chemotherapy‐naïve WTs are the only risk factors used for treatment stratification. However, they predict only less than one‐third of all relapsing patients, implying that other factors are involved in treatment failure. Previous studies have associated 1q gain with adverse outcome. Therefore, in this study, the role of 1q gain and other common cytogenetic aberrations (CAs) in WTs was investigated and related to follow‐up data from patients with WT treated in the United Kingdom; 19% (64/331) had 1q gain. Gain of 1q was significantly associated with 16q loss (P < 0.001) and 1p loss (P < 0.001). In multivariate analysis taking account of age, tumor stage, anaplasia, and common CA (e.g., 1p loss and 16q loss), 1q gain was independently associated with adverse event‐free survival [EFS; hazard ratio (HR) = 2.45, P = 0.02] and overall survival (HR = 4.28, P = 0.004). Loss of 14q was independently associated with an adverse EFS (HR = 4.0, P = 0.04). Gain of 1q is a marker of poor prognosis in WTs, independent of high tumor stage and anaplasia which remain the overarching adverse prognostic factors. Confirmation in other studies is necessary before future therapeutic studies can incorporate 1q gain into new risk stratification schema. © 2013 Wiley Periodicals, Inc.